Analysis of the importance of social/racial quotas through ENEM's microdata mining - Vioti dos Santos, Vandeir; Notargiacomo, Pollyana (Informática na educação teoria & prática, 2023)
Educational data analysis can provide new metrics and provide relevant information for creating tools. These seek to develop students' specific skills with the aim of increasing performance, improving existing methodologies and, mainly, developing educational policies. Given this scenario, a study was carried out with the objective of measuring the impact of the economic and social situation of Brazilian students. The National High School Exam (ENEM), in Brazil, is used by the students as one of the routes to apply and enter the higher education system, and also as a way to obtain scholarships. The main objective of this article is to emphasize the importance of the presence of racial and social quotas, through the analysis of ENEM microdata with Artificial Intelligence tools, interrelating their impact to the laws no. 12.711/2012 and no. 12.990/2014, not yet renewed in the governmental sphere, responsible for determining the rules regarding quotas in Brazil.